Emerging potential of niosomes in ocular delivery. (2nd January 2021) - Verma, Amit; Tiwari, Ankita; Saraf, Shivani; Panda, Pritish Kumar; Jain, Ankit; Jain, Sanjay K.
ABSTRACT: Introduction: Niosomes have recently grabbed attention as one of the best tools for various site-specific drug delivery systems, including ophthalmic drug delivery. Surfactants (nonionic; tweens and spans) of different HLB values and cholesterol are the fundamental components for these formulations. It is an alternative controlled ocular drug delivery system to liposomes to overcome the problems associated with sterilization, large-scale production, and stability. It also enhances the adhesion or retention ability of drug at the ocular site. Hydrophilic or lipophilic or amphoteric drugs can be easily encapsulated in niosomes. Besides, niosomes are a leading vesicular system compatible with most of the drugs for site-specific delivery. Areas covered: This article reveals challenges and barriers for ocular drug delivery, various transporters and receptors present in the ocular region for the transportation of therapeutics as well as nutrients, and various method of preparations, loading methods and application potential of niosomes in ocular drug delivery. Expert opinion: Niosomes, a vesicular system offers numerous advantages and applicability because of its good stability, non-immunogenicity, permeation potential, and controlled release ability etc. This drug delivery system has been efficiently used in the treatment of many ocular diseases.